Sinistral portal hypertension - Thompson, Richard J (The Ulster Medical Society, 2006)
Sinistral, or left-sided, portal hypertension is a rare cause of upper gastrointestinal haemorrhage. There are many causes of sinistral portal hypertension. The primary pathology usually arises in the pancreas and results in compression of the pancreatic vein. This compression causes backpressure in the left portal venous system and subsequent gastric varices. Management is usually surgical to treat the underlying pathology and splenectomy to decompress the left portal venous system. This paper presents four cases of sinistral portal hypertension followed by a literature review of the reported causes and management issues.